The Impact of Natural Suckling on Milk Yield and Growth Rates of Kids of Nubian Goats (Journal of Veterinary Medicine and Animal Production, 2022)
This study was carried out to evaluate the effect of suckling on milk production of Nubian goats and growth rates of respective kids. The study involved 20 multiparous Nubian goats allocated randomly according to body weight and age to two equal groups of 10 does each. Group A suckled their kids for 13 weeks, while group B (control) was not suckled and their kids were reared artificially by bottle for 13 weeks. The results indicated a significant (P< 0.05) difference for the daily milk yield (kg\day) in favour of the suckled group. The recorded values were 1.07±0.3 versus 0.8±0.28 (kg\ day) for group A and B, respectively. The peak yield in group A and B was 1.5±1.1 and 1.2±0.1 (kg\day), respectively. The present study revealed significant (P